Inactivation of Competitive Decay Channels Leads to Enhanced Coumarin Photochemistry. Issue 35 (12th May 2022) - Klimek, Robin; Asido, Marvin; Hermanns, Volker; Junek, Stephan; Wachtveitl, Josef; Heckel, Alexander
Abstract: In the development of photolabile protecting groups, it is of high interest to selectively modify photochemical properties with structural changes as simple as possible. In this work, knowledge of fluorophore optimization was adopted and used to design new coumarin‐ based photocages. Photolysis efficiency was selectively modulated by inactivating competitive decay channels, such as twisted intramolecular charge transfer (TICT) or hydrogen‐bonding, and the photolytic release of the neurotransmitter serotonin was demonstrated. Structural modifications inspired by the fluorophore ATTO 390 led to a significant increase in the uncaging cross section that can be further improved by the simple addition of a double bond. Ultrafast transient absorption spectroscopy gave insights into the underlying solvent‐dependent photophysical dynamics. The chromophores presented here are excellently suited as new photocages in the visible wavelength range due to their simple synthesis and their superior photochemical properties. Abstract : To date, there is only little information on how to rationally optimize the uncaging efficiency of photocages. However, there are many studies that successfully optimized the performance of fluorophores. This study demonstrates that structural modifications inspired by the fluorophore ATTO 390 can lead to a one order of magnitude increase in the uncaging cross section of new coumarin photocages.